2014
DOI: 10.1016/j.bjp.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of quality of deer antler slices by using an electronic nose coupled with chemometric analysis

Abstract: Electronic noseDeer antler Lu-Rong Quality A B S T R A C T Deer antler is a precious animal-sourced traditional Chinese medicine. We aimed to rapidly assess the quality of deer antler slices by electronic nose so that we can ensure medical safety. In this study, response intensity of the electronic nose was favorably optimized, and samples were well assessed by using an electronic nose based on LDA model. The results obtained herein suggested that electronic nose could be an effective method to rapidly assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In CHM identification, E-nose has been used in identification [ 17 ], quality assessment [ 18 ], and geoherbalism evaluation [ 19 ] combined with various multiple mathematical algorithms, such as diffusion maps, or principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
“…In CHM identification, E-nose has been used in identification [ 17 ], quality assessment [ 18 ], and geoherbalism evaluation [ 19 ] combined with various multiple mathematical algorithms, such as diffusion maps, or principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, rare studies had reported about discrimination of animalsourced medicinal materials based on specific smells. We firstly established the electronic nose to assess the quality of different deer antler slices [13], and this study is the first attempt to test the electronic nose for discrimination of fake animal-sourced medicinal species. We previously had understood that LDA model was suitable for modeling of velvet antlers [13], so LDA directly was used to test their applicability of discriminating fake velvet antlers in this study.…”
Section: Resultsmentioning
confidence: 99%
“…A FOX-3000 (Alpha MOS, Toulouse, France), which consisted of a sampling apparatus, array of Table 2. The response values of samples of fake velvet antlers were recorded according to the previous work [13]. The data sets of official or authentic velvet antlers also referred to our previous work [13].…”
Section: Electronic Nosementioning
confidence: 99%
“…DNA fingerprinting and microsatellites (including restriction fragment length polymorphisms and amplified fragment length polymorphisms) are effective tools for distinguishing between plant populations. Fingerprinting analysis of traditional Chinese medicine (TCM) represents a comprehensive qualitative approach to species authentication and quality evaluation, and ensures a consistent quality of TCMs ( Wang et al., 2011 ; Xu et al., 2014 ). Gas chromatography (GC) is the preferred method for the analysis of volatiles because of its high reproducibility, while all other methods involve high capital costs, complex operations, and are time consuming ( Tao et al., 2014 ; Yang et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%